Aplicación e integración de los sistemas ISO 9001:2000 de gestión de calidad e iso 14001:2004 de gestión de medio ambiente, en una planta procesadora de productos de aceros - Huayamave, Marcela (2009)
Currently, companies are going through a period of positive changes. There, they have realized that the creation of products or services following traditional strategies is not enough to compete in the global market. In this context, the International Standards Organization (ISO) has created policies to standardize process to assure the quality of products and services. The firms may use these policies to be able to compete globally. The purpose of this thesis is the implementation and integration of two systems: Quality Management and Environmental Management in a steel products processing plant. The process requires a new style management that provides effective tools to integrate the employees to address this change successfully. Based on the concept of total quality, the methodology comprises the process administration. We classified the characteristics of the company in organizational, dynamic and fixed. Organizational characteristics define the activities, responsibilities and authority levels for each process. Dynamic characteristics establish the process to add value to the product. Finally, among fixed characteristics we found infrastructure, waste emissions and risks. At the end of the process we integrated Quality Management and Environmental Management systems. The result was the improved administration of the processes of the company. We have demonstrated that the integration of the systems start with the implementation of Quality Management. Thus, the firm has the bases to develop other systems to improve either manufacturing or service operations.